Effect of a new phacoemulsification and aspiration handpiece on anterior chamber stability. Issue 1 (January 2023) - Suzuki, Hisaharu; Igarashi, Tsutomu; Takahashi, Hiroshi
Abstract : Active Sentry, a new fluid dynamics mechanism, greatly contributes to anterior chamber stability even when occlusion occurs, suggesting its usefulness in cataract surgery with a low intraocular pressure. Abstract : Purpose: To evaluate the responsiveness of 3 phacoemulsification and aspiration (PEA) systems and a new handpiece to occlusion break by measuring anterior chamber depth (ACD) and intraocular pressure (IOP). Setting: Zengyo Suzuki Eye Clinic, Kanagawa, Japan. Design: Experimental study. Methods: ACD change during intentional occlusion breaks was observed and evaluated using the slit side view (SSV) method and IOP measurement with the Centurion Vision System (Group 1), Centurion Vision System with Active Sentry (Group 2), Infiniti Vision System (Group 3), and Constellation Vision System (Group 4). 5 eyes were included per group. Occlusion breaks were triggered at IOP of 30 mm Hg, vacuum limits of 550 mm Hg, and aspiration rate of 40 mL/min. ACD change ratio, surge duration, and surge volume were analyzed from videos of SSV and IOP measurement. Results: The smallest ACD change was observed in Group 2 with SSV. ACD change ratios in Groups 1 to 4 were 17.5% ± 3.9%, 7.3% ± 1.2%, 35.7% ± 9.5%, and 74.1 ± 7.7%, respectively. Surge duration and surge volume were calculated only for Groups 1 and 2 and were significantly lower in Group 2 than in Group 1 (0.32 ± 0.03 vs 1.17 ± 0.07 seconds; 18.91 ± 4.70 vs 45.70 ± 0.83 μL). In these 2 groups, ACD change ratio correlated with surge volume. Conclusions: This study evaluated the responsiveness of 3 PEA systems and a new handpiece to occlusion breaks by measuring IOP and ACD. The Active Sentry system was useful for maintaining the ACD even during occlusion breaks.